Associations between psychosocial factors and antiretroviral therapy outcomes differ by gender and sexual orientation among people living with HIV in British Columbia, Canada. Issue 2 (1st February 2023) - Closson, Kalysha; Nicholson, Valerie; Lee, Melanie; McLinden, Taylor; Cassidy-Matthews, Chenoa; G. Card, Kiffer; E. Marziali, Megan; Trigg, Jason; Wang, Lu; Parashar, Surita; S. G. Montaner, Julio; Gibbs, Andrew; et al.
ABSTRACT: Little is known about how the co-occurrence of psychosocial factors affect sub-populations of people living with HIV (PLWH). We used cross-sectional data from 999 PLWH, aged ≥19, accessing antiretroviral therapy (ART) in British Columbia, Canada (2007–2010) to examine associations between psychosocial factors and ART-related outcomes separately for trans/cis inclusive women; heterosexual men; and gay, bisexual, and other men who have sex with men (gbMSM). Multivariable logistic regression examined associations between psychosocial factors (0–3): any violence in the past 6 months, depressive symptoms in the past week, and current street drug use (heroin, crack, meth or speedball) with sub-optimal adherence (outcome 1: average annual ART adherence <95% from interview until end of follow-up, death, or December 31st, 2018) and ever viral rebound (outcome 2) adjusting for potential confounders. Of 999 PLWH (264 women, 382 heterosexual men, and 353 gbMSM), women and heterosexual men had significantly higher median counts than gbMSM. Overall, higher counts were associated with sub-optimal adherence (adjusted odds ratio [aOR] = 1.26/1-unit increase, 95%CI = 1.07–1.49). All effect estimates were of a greater magnitude among gbMSM, but not significant for women or heterosexual men, highlighting the need for population (e.g., gender and sexual orientation)-centered care and research.